Comparative study of “Commercially available mouthwashes with that of herbal mouthwashes” on pre-dominant oral cavity flora- Streptococcus species - Esha, M.K.; Anuradha, K. (International Journal of Scientific Research in Biological Sciences, 2019)
Oral cavity is a vital part of the body and contributes to total health and wellbeing. Poor oral health affects general health and leads to systemic diseases like dental caries. The association between oral diseases and oral cavity flora is well established. There are more than 700 species of bacteria which may affect oral cavity and a number are implicated in oral diseases. Dental caries are developed by micro-organisms like Streptococcus, Lactobacillus and Actinomycetes which can be inhibited with the use of herbal and commercial mouthwashes as they show anti-microbial activity. Many researchers studied effect of anti-microbial activity of plant extracts on microbial flora of oral cavity. However, the studies on green synthesis of silver nanoparticles from the plant extracts and its effect on microbial flora of oral cavity would be a significant finding as these nanoparticles are efficient at very low concentrations and can penetrate into dental cavities easily. The silver nanoparticles play a crucial role in dental field for not only controlling the pathogens but also in other applications of nano dentistry. The present study includes screening, isolation and identification of microbial flora of oral cavity and to determine the effect of silver nanoparticles on oral flora. 50 oral cavity samples of patients fitted with dental braces from Army College of Dental Sciences and other dental clinics were collected. Streptococcus species was the predominant bacteria found in all these samples and the same organism is selected for comparative study of effect of commercially available mouthwashes like Orarite, Histidine and Whisper mint with that of herbal products like Azadirachta indica (Neem), Ocimum santum (Tulsi), Mentha (Peppermint), Piper betle (Betel) and Syzigium aromaticum (Clove). The results demonstrated that herbal products have more anti-microbial activity on Streptococcus species than the commercially available mouthwashes. These plant products were further tested for green synthesis of silver nanoparticles. The Silver Nanoparticles produced were characterized by Spectrophotometric, and SEM analysis. The silver nanoparticles synthesized from these plant products are safe, efficient and economical to use in herbal mouthwash preparations for dental diseases.